The quality of teacher-made summative tests for Islamic education subject teachers in Palembang, Indonesia - Waty, Evy Ratna Kartika; Nengsih, Yanti Karmila; Handrianto, Ciptro; Rahman, M. Arinal (Jurnal Cakrawala Pendidikan, 2024)
Criticism of exams can be used to gauge student achievement for graduation. This study examined the quality of Summative Tests (ST) created by senior high school teachers in Palembang, Indonesia, specifically focusing on the Islamic Education subject. The evaluation criteria included item validity, reliability, discrimination index, and disruptive effectiveness. The analysis involved 800 answer sheets from 20 teachers. Results indicated that while 20 teachers achieved high reliability, two struggled with poor reliability in terms of disruptive effectiveness. Respondent 11 faced challenges with only 28% valid items and a moderate Cronbach's Alpha. Additionally, the disruptive effectiveness and discrimination index were poor. These findings suggest a need for teacher training to enhance skills in crafting and administering high-quality summative tests. The implications of these findings extend to improving teacher training and ensuring the effectiveness of summative assessments in gauging student achievements for graduation. The research contributes valuable insights into the complexities of teacher-created exams and offers a basis for enhancing the overall quality of education assessment practices.